2006
DOI: 10.1002/anie.200503602
|View full text |Cite
|
Sign up to set email alerts
|

A Biomimetic Model for the Active Site of Iron‐Only Hydrogenases Covalently Bonded to a Porphyrin Photosensitizer

Abstract: Efficient communication: The first porphyrin‐photosensitizer‐containing biomimetic model for the active site of Fe‐only hydrogenases has been synthesized and structurally characterized (see picture). Its fluorescence spectrum reveals that an efficient electronic communication occurs between the porphyrin unit and the covalently linked diiron–azadithiolate moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 36 publications
2
93
0
Order By: Relevance
“…These latter values are within the range of previous studies on the ironsulfur cluster-free hydrogenase from methanogenic archaea (δ = 0.04, ∆E Q = 0.65). [34] The IR spectrum of 3a in dichloromethane shows three metal-carbonyl stretching bands in the metal-CO region at 2077, 2040 and 2000 cm -1 (Table 2), which correlate well with the published values of Fe 2 (CO) 6 -(thiolato) 2 compounds, [10,24,[35][36][37] and furthermore are similar to the values obtained by Happe et al on the H 2 ase enzyme of Chromatium vinosum. [38] The solid-state structure of 3a has been determined by single-crystal X-ray diffraction and is shown in Figure 2.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These latter values are within the range of previous studies on the ironsulfur cluster-free hydrogenase from methanogenic archaea (δ = 0.04, ∆E Q = 0.65). [34] The IR spectrum of 3a in dichloromethane shows three metal-carbonyl stretching bands in the metal-CO region at 2077, 2040 and 2000 cm -1 (Table 2), which correlate well with the published values of Fe 2 (CO) 6 -(thiolato) 2 compounds, [10,24,[35][36][37] and furthermore are similar to the values obtained by Happe et al on the H 2 ase enzyme of Chromatium vinosum. [38] The solid-state structure of 3a has been determined by single-crystal X-ray diffraction and is shown in Figure 2.…”
Section: Resultssupporting
confidence: 88%
“…[17][18][19][20][21] To this end, diiron model compounds or even ruthenium complexes (for which no natural precedent exists) with a variety of unnatural ligands such as phosphanes and carbenes have been employed. [18,19,22,23] Other examples have reported attachment of the active-site cluster models to electrochemical sensors such as porphyrins, [24] a ruthenium-based photosentizer [25][26][27] or even models of the natural [Fe 4 S 4 ] cubane unit. [28] In the bimetallic [NiFe] H 2 ase, the Ni atom is coordinated to four sulfur atoms from cysteine amino acids, two of which bridge the Fe atom.…”
Section: Introductionmentioning
confidence: 98%
“…Reaction of [(μ-R 1 S)(μ-CO)Fe 2 (CO) 6 ] -with (μ-S 2 )Fe 2 (CO) 6 forms a tetrairon anion (μ-R 1 S)Fe 2 (CO) 6 (μ 4 -S)Fe 2 (CO) 6 (μ-S -). This anion further reacts with electrophiles R-X or RCOCl to afford (μ-R 1 S)Fe 2 (CO) 6 (μ 4 -S)Fe 2 (CO) 6 (μ-and 2, (μ-PhCH 2 CO)Fe 2 (CO) 6 (μ 4 -S)Fe 2 (CO) 6 (μ-CN(C 3 H 5 ) 2 ). Their structures were unambiguously determined by X-ray crystallography.…”
Section: Syntheses Of Complexesmentioning
confidence: 99%
“…[18] Moreover, the reaction of (μ-η 2 -R 1 CH=CH)(μ-Cl)Fe 2 (CO) 6 with (μ-RS)Fe 2 (CO) 6 (μ-S -) generated from the reaction of (μ-S 2 )Fe 2 (CO) 6 with RLi or RMgX gives (μ-η 2 -R 1 CH=CH)-Fe 2 (CO) 6 (μ 4 -S)Fe 2 (CO) 6 (μ-SR). [19] Particularly, the reaction of (Et 4 N) 2 Fe 2 (CO) 8 and ClSCNMe 2 can afford (μ-Me 2 NC)-Fe 2 (CO) 6 (μ 4 -S)Fe 2 (CO) 6 (μ-SCNMe 2 ) albeit in a low yield. [20] Surprisingly, the reaction of Fe 3 (CO) 12 with (C 3 H 5 ) 2 NCS 2 K in THF at room temperature forms a red-brown solution.…”
Section: Syntheses Of Complexesmentioning
confidence: 99%
“…Particular emphasis has been placed on variations of L, especially tertiary phosphines [1][2][3], but also isocyanides [4,5], N-heterocyclic carbenes [6][7][8][9], and cyanide [10][11][12][13]. While much effort has focused on functionalizing the dithiolate ligand [14][15][16][17][18][19][20], relatively little work has examined the possibility of replacing the thiolates with other bridging groups [21]. Best and coworkers demonstrated that the corresponding phosphides Fe 2 (PR 2 ) 2 (CO) 6 and [Fe 2 (PR 2 ) 2 (CO) 6 H] − are effective catalysts for hydrogen evolution [22].…”
mentioning
confidence: 99%